K ETYMOLOGIJI PSŁ. *SLĚPЪ/SLEPЪ - WORNAR, EDWARD (Slavia Occidentalis, 2020)
This article explains the hitherto unexplained variation of the root *slep/slěp- ‘blind’ which results from an old opposition of the causative (lengthened grade) vs. regular root (regular grade). This indicates a connection with the Lithuanian silpnas as a zero-grade root for the Slavic word which previously had no convincing parallels in other languages. Semantically, a connection with words meaning ‘sticky’ (as postulated by Šewc 1978 and others) should be rejected: they are neither phonetically nor semantically convincing. The preference is for the interpretation of blindness as a special kind of weakness.